An Overlooked Detail: Sleep and Quality of Life in Patients with Atrial Fibrillation - Sayin Kasar, Kadriye; Ozer, Serap (Puerto Rico Health Sciences Journal, 2023)
Objective: The aim of this study was to investigate sleep quality and quality of life, sociodemographic variables that may affect sleep quality, and the relationship between sleep and quality of life in patients with atrial fibrillation (AF). Materials and Methods: This descriptive cross sectional study had a sample of 84 individuals (AF patients from April 2019–January 2020). The Patient Description Form, the Pittsburgh Sleep Quality Index (PSQI), and the EQ-5D health-related quality of life instrument were used to collect data. Results: The mean total PSQI score was 10.72 (±2.73), we found that most of the participants (90.5%) had poor sleep quality. While there was a significant difference between the sleep quality and employment status of the patients, there was no significant difference between age, gender, marital status, education level and income status, comorbidity, family history of AF, continuously used medication, non-drug AF treatment, and AF duration (P > .05). The sleep quality of those working in any job was better than of their non-working counterparts. Regarding the correlation between sleep quality and quality of life, a medium-level negative correlation was found between the patients’ total mean PSQI and EQ-5D visual analogue scale scores. However, no significant correlation was found between the total mean PSQI and EQ-5D scores. Conclusion: We found that sleep quality in patients with AF was poor. In these patients, sleep quality should be evaluated and taken into consideration as a factor that affects quality of life.